Chemical stiffening of constructs between polymeric microparticles based on a hyaluronic acid derivative and mesenchymal stem cells: rheological and in vitro viability studies. Issue 3 (12th November 2018) - Palumbo, Fabio S; Agnello, Stefano; Fiorica, Calogero; Pitarresi, Giovanna; Giammona, Gaetano
Abstract: Our research group has recently developed microparticles of a hyaluronic acid derivative used for bottom‐up growth of microparticles/human mesenchymal stem cells (hMSCs). In this work, we investigated a strategy to increase the stiffening of aggregated constructs between microparticles and hMSCs. In particular, we applied a Michael‐type crosslinking procedure between microparticles to allow a chemically driven and cell‐compatible stiffening of constructs. Two batches of microparticles were functionalized with thiol and maleimide groups, respectively, and were then mixed to allow chemical crosslinking. The adhesion of hMSCs was controlled through addition of the adhesive peptide cyclo(‐Arg‐Gly‐Asp‐D‐Phe‐Cys) (cyRGDC). Rheological measurements performed in this study showed that the chemical stiffening strategy allows the G ′ modulus of bottom‐up growing constructs to be increased, while viability tests suggest that the chemical procedure did not negatively affect cell viability compared with constructs obtained without chemical crosslinking. © 2018 Society of Chemical Industry Abstract : We describe a cytocompatible crosslinking procedure for stiffening polymeric microparticle/human mesenchymal stem cell (hMSC) constructs. The adhesion of hMSCs was controlled thanks to the addition of the adhesive peptide cyRGDC. The rate of stiffening was followed through rheological measurements.